Spiritual evolution : scientists discuss their beliefs - Templeton, John, 1912-2008; Giniger, Kenneth Seeman, 1919- (Templeton Foundation Press ; Published in association with the K.S. Giniger Co., 1998)
Spiritual Evolution: Scientists Discuss Their Beliefs describes the intellectual and emotional journeys traveled by esteemed scientists worldwide. Authors share the personal steps they have taken to blend an understanding of the Divine with their scientific perspectives. Charles Birch, S. Jocelyn Bell Burnell, Larry Dossey, Owen Gingerich, Peter E. Hodgson, Stanley L. Jaki, Arthur Peacocke, John Polkinghorne, Russell Stannard, and Carl Friedrich von Weizsäcker offer accounts of their spirituality and scientific inquiry. Noting the impact of religious upbringing, academic and spiritual ment.